Dysregulation of the RANKL/RANK/OPG axis in thalassemia intermedia patients - Alfaqih, Mahmoud A. (BMC Res Notes, 2018)
OBJECTIVE: Thalassemia intermedia (TI) describes a disease ranging in severity between β thalassemia major (TM) and β thalassemia trait. Osteoporosis is observed in TI and TM. The exact reason of osteoporosis in TI could be hypogonadism and/or an increase in erythropoietin (EPO) levels. The carboxy-terminal collagen cross links (CTX), a marker of bone resorption, and the N-terminal propeptide of type 1 collagen (P1NP), a marker of bone formation are serum markers of osteoporosis. The receptor activator of NF-kappaB ligand (RANKL)/receptor activator of NF-kappaB (RANK)/osteoprotegerin (OPG) axis plays an important role in metabolic bone diseases. Herein, we tested the relationship between the RANKL/RANK/OPG axis and the bone-turnover markers CTX and P1NP in TI. RESULTS: We recruited 44 TI patients and 33 non-thalassemic controls and measured the serum levels of hemoglobin, sex steroid hormones, CTX, P1NP, RANKL and OPG. We then used a general linear model to test the association of the above variables with CTX and P1NP as outcome variables. We showed that EPO levels were the strongest predictor of CTX change (P < 0.000), followed by RANKL (P = 0.017). On the other hand, RANKL was the strongest predictor of P1NP change (P < 0.000), followed by OPG (P = 0.009) and EPO (P = 0.024).